2006
DOI: 10.1158/1535-7163.mct-05-0164
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic homoharringtonine induces apoptosis via inhibition of protein synthesis and triggers rapid myeloid cell leukemia-1 down-regulation in myeloid leukemia cells

Abstract: Semisynthetic homoharringtonine (ssHHT) is now being evaluated in phase II clinical trials for the treatment of chronic myelogenous leukemia and acute myelogenous leukemia patients. Here, we examined the mechanism of the apoptosis induced by ssHHT in myeloid leukemia cells. First, we have shown that ssHHT induces apoptosis in HL60 and HL60/MRP cell lines in a time-and dosedependent manner, and independently of the expression of Bax. The decrease of mitochondrial membrane potential and the release of cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 24 publications
5
78
1
Order By: Relevance
“…52 This phenomenon occurred in the absence of Bcl-2, Bax, Bcl-x L , mitogen-activated protein kinase, and AKT down-regulation before 8 hours posttreatment. These effects were replicated in primary cells obtained from patients with AML 51 and patients with CML. 53 However, other reports have indicated that the proapoptotic activity of HHT may involve not only the activation of caspase-9, caspase-3, and PARP but also the activation of caspase-8, thus involving both intrinsic and extrinsic apoptotic pathways, as demonstrated in human myeloma cell lines and tumor cells from patients with recurrent/refractory multiple myeloma.…”
Section: Phase 2 Studies Of Intravenous Hht In CMLmentioning
confidence: 75%
See 1 more Smart Citation
“…52 This phenomenon occurred in the absence of Bcl-2, Bax, Bcl-x L , mitogen-activated protein kinase, and AKT down-regulation before 8 hours posttreatment. These effects were replicated in primary cells obtained from patients with AML 51 and patients with CML. 53 However, other reports have indicated that the proapoptotic activity of HHT may involve not only the activation of caspase-9, caspase-3, and PARP but also the activation of caspase-8, thus involving both intrinsic and extrinsic apoptotic pathways, as demonstrated in human myeloma cell lines and tumor cells from patients with recurrent/refractory multiple myeloma.…”
Section: Phase 2 Studies Of Intravenous Hht In CMLmentioning
confidence: 75%
“…sHHT currently is known as omacetaxine The mechanism of action of omacetaxine involves induction of apoptosis in a Bax-independent fashion through mitochondrial disruption and the release of cytochrome c, leading to caspase-9 and caspase-3 activation in HL60 and HL60/MRP myeloid leukemia cell lines. 51 However, omacetaxine did not activate caspase-8 or promote BH3-interacting domain death agonist (Bid) cleavage. The early event that triggered omacetaxine mepesuccinate-induced apoptosis was the down-regulation of Mcl-1, which originally was identified as an antiapoptotic Bcl-2 family protein during differentiation of myeloid cells.…”
Section: Phase 2 Studies Of Intravenous Hht In CMLmentioning
confidence: 99%
“…Franck E. Nicolini, 1 H. Jean Khoury, 2 Luke Akard, 3 Delphine Rea, 4 Hagop Kantarjian, 5 Michele Baccarani, 6 Janis Leonoudakis, 7 Adam Craig, 8 Annie-Claude Benichou, 8 …”
mentioning
confidence: 99%
“…24 To define the role of proteasomal degradation for the OM-induced cCRbc-downregulation in hematopoietic cells, we performed combination experiments with the proteasome-inhibitor MG-132 and OM. For this end we treated Ba/F3p210 cells with 10 mM MG-132 1 h prior adding 50 nM of OM.…”
Section: Resultsmentioning
confidence: 99%